Nanostructural, Chemical, and Mechanical Features of nc-Si:H Films Prepared by PECVD - Jong-Ick Son; Hee-Jong Nam; Nam-Hee Cho (International Journal of Photoenergy)
This study examined the effects of film thickness on the nanostructural, chemical, and mechanical features of nc-Si:H films deposited by plasma-enhanced chemical vapor deposition. SiH4 and H2 were used as the source gases, and the deposition time was varied from 10 to 360 min. The mean nanocrystallites size in the Si films increased from ~6 to ~8 nm with increasing film thickness from 85 to 4150 nm. Moreover, the nanocrystallite concentration and elastic modulus increased from ~7.5 to ~45% and from 135 to 147 Gpa, respectively. In the 4150 nm thick film, the relative volume fraction of Si nanocrystallites and relative fraction of Si–H bonds in the films were approximately ~45% and ~74.5%, respectively.